2007
DOI: 10.1002/ejoc.200700678
|View full text |Cite
|
Sign up to set email alerts
|

The (Porphyrin)ruthenium‐Catalyzed Aziridination of Olefins Using Aryl Azides as Nitrogen Sources

Abstract: Aryl azides have been used as atom-efficient nitrene transfer reagents in the (porphyrin)ruthenium-catalyzed amination of olefins. Several azides, olefins and [Ru(porphyrin)CO] complexes were tested to investigate the scope and limits of the reaction. Quantitative yields and short reaction times were achieved by using terminal olefins and aryl azides bearing electron-withdrawing groups on the aryl moiety. The reactions were influenced by steric factors. Internally disubsti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 79 publications
4
49
0
2
Order By: Relevance
“…With an oxidant loading of 2 equiv, an examination of solvent effects showed that reactions carried out in CHCl 3 and CH 2 Cl 2 gave the desired aziridine 3a in near quantitative yields (entries 10 and 11). In contrast, lower product yields of 21-66% were obtained when C 6 H 6 , MeNO 2 1,4-dioxane, and 1,2-dichloroethane were employed as solvents (entries [6][7][8][9].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 86%
See 2 more Smart Citations
“…With an oxidant loading of 2 equiv, an examination of solvent effects showed that reactions carried out in CHCl 3 and CH 2 Cl 2 gave the desired aziridine 3a in near quantitative yields (entries 10 and 11). In contrast, lower product yields of 21-66% were obtained when C 6 H 6 , MeNO 2 1,4-dioxane, and 1,2-dichloroethane were employed as solvents (entries [6][7][8][9].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 86%
“…[1][2][3][4][5][6][7][8][9][10][11] The ability of aziridines to undergo regio-and stereoselective ring opening reactions also renders this class of compounds as invaluable building blocks in organic synthesis. For this reason, the development of novel synthetic routes for the preparation of aziridines has received significant attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Ru(porphyrin)CO complexes 36-47 (Chart 1) were very active for the synthesis of N-aryl aziridines obtained from the reaction of alkenes with aryl azides [44].…”
Section: Rutheniummentioning
confidence: 99%
“…The aziridine synthesis was performed by a two-step process where the aniline was first converted into the corresponding aryl azide, by using a modification of a reported method [54], and then the Ru(TPP)CO (36)-catalysed reaction of the azide with the alkene produced the desired aziridine molecule [55,56]. Yields and selectivities of the second step of the flow process were comparable to those achieved by employing the standard batch procedure [44] and the reaction was performed in alkene as the reaction solvent which was easily recycled in the continuous flow process (Scheme 13).…”
Section: Scheme 10mentioning
confidence: 99%